MAIN PRIORITIES FOR THE FORMATION OF ENVIRONMENTAL CULTURE OF STUDENTS OF MEDICAL COLLEGES (Innovative professional education, 2023)
A comprehensive solution to the problem of environmental education requires the interconnection of all existing trends, the integration of valeology, ecology and medicine. Various psychological factors and mechanisms that contribute to the formation of an ecocentric type of environmental education serve as the psychological basis for the selection of the content of ecological and valeological education, which form ecological consciousness. The ontogenetic regularities of the formation of ecological culture in youth actualize the understanding of the student's personal position, attracting the search for harmony in the natural world and interaction with the natural world.
Keywords: ecological culture, student, medical college, human health